The Violation of Maxim by the Characters in the Netflix Series Inventing Anna - Putri, Made Diva Suniantari; Dewi, A.A. Sg. Shanti Sari; Aryawibawa, I Nyoman (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2024)
This study aims to identify the types of conversational maxims violated by the characters in the Inventing Anna series and to find out the motives behind the violation of maxims. This research used a qualitative approach because it involves descriptive and non-numerical analysis. Documentation method, note-taking technique, and content analysis are applied to collect and analyze the data. The documentation method was applied to find information from a video (Inventing Anna series) and its transcription. Meanwhile, the note-taking technique was to note down the conversations or utterances of the characters in the series that contain maxim violation. The main theory used in this research is Maxim Violation by Paul Grice (1975). The study analyzed four characters from the series and found 14 maxim violations in the characters’ utterances from Inventing Anna series. There are 5 violating maxim of quality, 2 violating maxim of quantity, 2 violating maxim of manner, 3 violating maxim of relation, and 2 violating several maxims in one conversation. There is a high possibility of violating more than one maxim in one conversation. The motives for violating a maxim based on the analysis are to escape bad situations, avoid getting involved in any trouble or scandal, face-saving act (maintain a good image), convince someone, get recognition, gain sympathy, and distract or manipulate the interlocutor. Keywords: Maxim Violation, Motives, Series, Characters